2013
DOI: 10.1111/ejhf.37
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness and risk of heart failure: a population‐based follow‐up study

Abstract: Aim To examine the relationship between cardiorespiratory fitness (CRF) and risk of incident heart failure (HF). Methods and results Cardiorespiratory fitness, as measured by maximal oxygen uptake (VO2max), was assessed at baseline in a prospective cohort of 1873 men aged 42–61 years without HF or chronic respiratory disease. During a mean follow‐up of 20.4 years, 152 incident HF events were recorded. Within‐person variability was calculated using data from repeat measurements taken 11 years apart. The age‐adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 59 publications
6
88
0
2
Order By: Relevance
“…They observed that lower physical activity, assessed with a standardized validated questionnaire, is associated with higher incidence of HF. More recently, Khan et al 12. in 2014 evaluated, in a first population‐based prospective study, 1873 men (aged 42–61) from eastern Finland to assess the prospective associations (follow‐up of 20.4 years) of cardiorespiratory fitness and the risk of HF.…”
Section: Before Heart Failure Onset (Past): Exercise As a Tool For Prmentioning
confidence: 99%
“…They observed that lower physical activity, assessed with a standardized validated questionnaire, is associated with higher incidence of HF. More recently, Khan et al 12. in 2014 evaluated, in a first population‐based prospective study, 1873 men (aged 42–61) from eastern Finland to assess the prospective associations (follow‐up of 20.4 years) of cardiorespiratory fitness and the risk of HF.…”
Section: Before Heart Failure Onset (Past): Exercise As a Tool For Prmentioning
confidence: 99%
“…[15][16][17] In contrast, the role of PA in reducing risk of HF has not been emphasized in existing guidelines and public health recommendations. 15 Although observational cohort studies have reported an inverse association between higher levels of PA and HF risk, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] a comprehensive assessment of the quantitative dose-response association between PA and HF risk has not been previously reported. Understanding this relationship is important because recent studies suggest that there may be important differences in the mechanisms through which PA modifies HF risk and CHD risk, 20 and the dose of PA needed to significantly lower HF risk may differ from that currently recommended to reduce CHD risk.…”
Section: Editorial See P 1777 Clinical Perspective On P 1794mentioning
confidence: 99%
“…One of the studies was US based (including a multiethnic population) 25 and the other was from Finland. 26 These studies included participants from both the sexes aged ≥45 years, with a majority of white race and a follow-up period of 6.5 to 20.4 years.…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%
“…Fitness was assessed through maximal oxygen uptake, VO 2 max (Table 2). 25,26 The ascertainment of HF was mostly based on hospital or death records, with only 1 study distinguishing type of HF into HF with reduced ejection fraction versus HF with preserved ejection fraction. 17 The degree of covariate adjustment varied across studies, with 8 studies accounting for intermediate states such as coronary heart disease (CHD) either through adjustment 14,18,21,24 or restriction of analyses to those with nonischemic HF 16,20,23 or exclusion of those with CHD at baseline (either as part of the original study design or a subgroup analysis).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation